Distribution of leaf litter spider (Araneae) in treefall gaps and on adjacent forest in an atlantic rainforest remnant in Bahia State, Brazil - PERES, Marcelo Cesar Lima; SOUZA-ALVES, João Pedro; BENATI, Katia Regina; DIAS, Marcelo Alves; ALVES, Alder Oliveira; MÁXIMO, Carolina Oliveira; BRESCOVIT, Antônio Domingos (Revista Biociências, 2010)
We compared the species distribution of leaf litter spider between adjacent forests and treefall gaps in an Atlantic Forest urban remnant in the Brazilian State of Bahia. The spiders were extracted from the leaf litter using a Berlese funnel from January to December, 2004. Each site was evaluated throughout the sampling period by measuring or estimating the microhabitat and microclimate variables of the treefall gaps and adjacent forest. The variables measured obtained a statistical difference (T= -2.4742605; P= 0.020855). A total of 550 spiders were collected, distributed among 15 families. A hundred and twenty one adult specimens were collected, 60 being in adjacent forest and 61 in treefall gaps. According to analysis, significant differences cannot be observed among sites with regard to abundance and number of spider species. However, there was a large number of exclusive species in both environments, 31.67% of all the species collected in adjacent forest and 26.53% of all species collected in treefall gaps, suggesting that the gaps created environmental differentiated structures that increase the diversity of spiders in Neotropical forest. Key words: natural disturbance, Metropolitan Park of Pituaçu, habitat selection.